A Study to Evaluate the Effectiveness of Planned Teaching Program on Knowledge Regarding Coronavirus Disease 2019 among B.Sc. Nursing 1st Year Students in Government College of Nursing, New Tehri, Uttarakhand, India - Jugran, Soniya; Joshi, Durga; Panwa, Shweta; Negi, Anchal; Bala, Deepti; Singh, Gopal; Pal, Jaya; Panwar, Manisha; Chauhan, Neelam; Rawat, Neha; et al. (Indian Journal of Nursing Sciences, 2024)
Aim: The study aims to evaluate the effectiveness of planned teaching program (PTP) on knowledge regarding coronavirus disease 2019 (COVID-19) among B.Sc. Nursing 1st year students in Government College of Nursing, New Tehri, Uttarakhand, India. Methodology: A quasi-experimental one-group pretest-posttest research design and quantitative research approach were used in the study. The sample consisted of 45 students of B.Sc. Nursing 1st year and was selected through convenient sampling method. The data were collected through online questionnaire method. Results: The data were analyzed by descriptive and inferential statistics. Assessment of the pre-test knowledge revealed that 20% had good knowledge, 68.89% had average knowledge, and 11.11% had poor knowledge. Assessment of the post-test knowledge revealed that 82.22% had good knowledge, 17.78% had average knowledge, and 0% had poor knowledge. The mean pre-test knowledge score was 15.86 with mean percentage 35.24% and standard deviation of ±4.46. The mean post-test knowledge score was 25.06 with mean percentage 55.68% and standard deviation of ±3.49. The paired t-test was used to find out the effectiveness of PTP. The findings revealed that paired t-test values were 14.82 at P < 0.0001 which was highly significant and Chi-square value 15.226 revealed that there was significant association between pre-test knowledge score with the selected demographic variable, that is, source of information. Conclusion: The study highlights that the students were able to gain knowledge regarding COVID-19 through PTP.